Reflexividade e constituição do mundo social: Giddens e Bourdieu (breves interpretações) - Flávio Ramos; Sérgio S. Januário (Ciências Sociais Unisinos)
This paper refers to a theoretical debate between Anthony Giddens and Pierre Bourdieu. The central issue has to do with reflectivity as a phenomenon that constitutes the social world as a dialogic potential of transformation and maintenance of social life. In a more specific way, it discusses the following question: Are social agents relatively free to introduce themselves to the social world by changing it creatively or are they reflexes of fixed and structuring structures (i.e., structures in a transformation process)? Obviously the article will not answer these questions completely, as they are too complex and have been intensively discussed for a long time by thinkers who have devoted their academic lives to this topic.